SETTING TIME, FLOWABILITY, AND SOLUBILITY OF EPOXY RESIN-BASED SEALER MIXED WITH CHITOSAN NANOPARTICLES - RATIH, DIATRI NARI; ENGGARDIPTA, RARAS AJENG; KUSUMO, ADI NUGROHO HENDRO; HADRIYANTO, WIGNYO (International Journal of Applied Pharmaceutics, 2021)
Objective: The purpose of this study was to investigate the effect of the incorporation of chitosan nanoparticles into epoxy resin-based sealer on its setting time, flowability and solubility. Methods: This study was divided into three evaluations: setting time, flowability, and solubility of sealers. Each study used 20 samples, which were divided into two groups. Group 1, epoxy resin-based sealers, and group 2, epoxy resin-based sealers mixed with chitosan nanoparticles. The Gilmore needle was used to observe the setting time, a simple press method based on ISO 6876 was employed to evaluate the flowability of the sealer, and the solubility test, which was according to ISO 6876 standard, was used to determine the solubility of sealers. The surface structure of the sealers before and after the solubility test was observed under Scanning Electron Microscopy (SEM). The data obtained from each study were analyzed by an unpaired t-test with a degree of significance of 95%. Results: The results showed that the setting time of epoxy resin and epoxy resin incorporated with chitosan were 567±30.20 and 572.5±27.91 min, flowability was 25.06±0.89 and 23.18±1.06 mm, and solubility was 0.0051%±0.0016 and 0.0045%±0.0018, respectively. No significant difference occurred between epoxy resin-based sealer and epoxy resin-based sealer mixed with chitosan nanoparticles in setting time, flowability, and solubility of sealers (*P>0.05). Conclusion: The incorporation of chitosan nanoparticles produced a similar effect in setting time, flowability, and solubility as the epoxy resin-based sealer. Thus, epoxy resin-based sealer mixed with chitosan nanoparticles had acceptable properties in setting time, flowability, and solubility based on ISO 6876 standards.